The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0103-20032004000100002
|View full text |Cite
|
Sign up to set email alerts
|

Curva de rendimentos: uma análise no mercado de trabalho urbano e rural no Brasil (1981/ 99)

Abstract: O mercado de trabalho está sujeito a constantes variações nos níveis de emprego e salários reais frente aos choques econômicos. As políticas macroeconômicas, sejam elas fiscais, monetárias ou cambiais, têm efeito sobre o emprego e o salário devido à interação entre os vários mercados. Segundo a abordagem neoclássica, qualquer rigidez nesses mercados deve ocasionar o desemprego dos fatores utilizados, principalmente o desemprego de mão-de-obra. Se a economia funciona, portanto, com preços flexíveis, choques de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…For the same period and with similar methodology, Souza and Machado (2004) estimate an unemployment elasticity estimate of -0.23 for urban areas and -0.06 for rural areas, a clear reflection of the concentration of informal jobs with low payments in rural areas. Reis (2006) uses aggregated data for the 1990-1999 period in order to estimate a dynamic wage curve for different skill levels.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For the same period and with similar methodology, Souza and Machado (2004) estimate an unemployment elasticity estimate of -0.23 for urban areas and -0.06 for rural areas, a clear reflection of the concentration of informal jobs with low payments in rural areas. Reis (2006) uses aggregated data for the 1990-1999 period in order to estimate a dynamic wage curve for different skill levels.…”
Section: Introductionmentioning
confidence: 98%
“…Previous literature on the wage curve for Brazil includes Garcia (2002), Souza and Machado (2004), Reis (2006), Santolin and Antigo (2009) and Silva and Monsueto (2012). All of these studies use the same survey (Brazilian National Household Survey).…”
Section: Introductionmentioning
confidence: 99%
“…Wage determination in Brazil has changed significantly over the past few decades (Carneiro & Henley, 1998), with unions acting more intensively in the bargaining process after the mid-1990s. Souza and Machado (2004) found that labor markets in urban areas (À0.23) were much more flexible than those in rural areas (À0.06) (PNAD data, 1981(PNAD data, -1999. Santolin and Antigo (2009) found that the wage curve seems to be non-dynamic in six metropolitan regions (PNAD data, 1997(PNAD data, -2005, but there is a higher wage flexibility for the whole group of workers (À0.15) than for formal workers (À0.05).…”
mentioning
confidence: 99%